2021
DOI: 10.14429/dsj.71.15403
|View full text |Cite
|
Sign up to set email alerts
|

Secret Key Generation Schemes for Physical Layer Security

Abstract: Physical layer security (PLS) has evolved to be a pivotal technique in ensuring secure wireless communication. This paper presents a comprehensive analysis of the recent developments in physical layer secret key generation (PLSKG). The principle, procedure, techniques and performance metricesare investigated for PLSKG between a pair of users (PSKG) and for a group of users (GSKG). In this paper, a detailed comparison of the various parameters and techniques employed in different stages of key generation such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Mai et al evaluated how different types of riblets on submarine surfaces impact drag force, which had a direct impact on the operating efficiency of the submarine [4]. Several studies have suggested that incorporating compliant material surfaces can result in a significant reduction of drag, estimated to be in the range of 10-12% compared to a rigid surface [5]. After a comprehensive comparison, it can be inferred that DR through coatings holds greater potential for development in various fields, as it does not require any alteration to the structure of the object undergoing DR. [6] developed a new polymer coating which can attach to any substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Mai et al evaluated how different types of riblets on submarine surfaces impact drag force, which had a direct impact on the operating efficiency of the submarine [4]. Several studies have suggested that incorporating compliant material surfaces can result in a significant reduction of drag, estimated to be in the range of 10-12% compared to a rigid surface [5]. After a comprehensive comparison, it can be inferred that DR through coatings holds greater potential for development in various fields, as it does not require any alteration to the structure of the object undergoing DR. [6] developed a new polymer coating which can attach to any substrate.…”
Section: Introductionmentioning
confidence: 99%